Effect Of Attendance Applications mobile Online (Akku Mobile) On Official Discipline At The Indramayu District Inspectorate - Setiadi, Ade; Firmasnyah, Farid Indra; Kusuma, Nurul Rahmah; Fauzia, Rizki Rahmah (Jurnal Manajemen Pelayanan Publik, 2024)
Employee attendance discipline is the main indicator for knowing an employee's responsibilities. Based on observations at the Indramayu Regency Inspectorate, employee discipline in terms of attendance is still not optimal. Therefore, a policy of using electronic presence, namely an online application (Akku Mobile) has been implemented by all ASN in the Indramayu Regency Government, which is directly recorded on the BKPSDM server. The purpose of this research is to determine the effect of the Online Attendance Application (Akku Mobile) on employee discipline at the Indramayu Regency Inspectorate. The research method used is an explanatory quantitative approach to see the influence of the Online Attendance Application (Akku Mobile) on employee discipline at the Indramayu Regency Inspectorate. The data source comes from primary sources through closed questionnaires. The results of this research show that there is a positive and significant influence between the use of the Akku Mobile application on employee discipline at the Indramayu Regency Inspectorate of 0.004, while the correlation level is weak at 0.326 or only 32.6%, and the application usage variable (Akku Mobile) can only explain This relationship is 10.6% towards increasing employee discipline, while the remaining 89.4% is explained by other factors outside this research.